Development of a mobile gamma-ray LaBr3(Ce) detector for in-situ radionuclide analysis at TENORM contamination sites - Van Niekerk, Ferdinand (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.